Sejarah Peranan Perempuan dalam Hijrah Rasulullah SAW pada 622 M - Rubiyanah Rubiyanah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2010)
This article discusses the period of Rasulullah saw hijriah which is an important moment in the history of Islam. The word hijriah means physically move to another place. Rasulullah saw and his companions moved from Mekkah to Yastrib which in 622 became Madinah. After the decease of Rasulullah, the context of hijrah changed; first, leaving a place full of kafir to a place full of Muslim, like the hijrah of Rasulullah saw from MEkkah to Madinah. Second, leaving bad behavior and sins to virtue Allah commands as explained in al-Qur'an; He said;